Ionisation loss and shock excitation of 4420Са I and 4420Са II atoms in cold remnants of type II supernovae - Doikov, D. N.; Andrievsky, S. M. (Одеські астрономічні публікації, 2017)
The light emission (“glow”) of cold dusty plasma of the remnant of SN 1987A was confirmed by the Hubble Space Telescope observations on 7th January, 1995. In particular, Ca I and Ca II lines were recorded and identified in the spectrum of the supernova’s envelope. The period of complete hydrogen recombination in the remnant is 800 days. Thus, it is only radioactive decay that could be a primary source of the plasma light emission at the moment of observation. This paper describes the conditions of shock excitation and recombination of 4420Ca resulted from the decay of radioactive 4422Ti travelling in the remnant’s cold dust. The overionisation in the remnant resulted from the motion of the 4420Ca recoil nucleus, as well as its impact on the spectrum formation, was studied. It has been shown that the calcium lines are formed by the 4420Ca II ion in the inner layers of the remnant. We have reached the conclusion that the Ca I/Ca II line strength ratio corresponds to the isotopic abundance ratio [4420Ca] /[4420Ca] in Type II supernova remnants.